Europe, America, and Technology: Philosophical Perspectives
VIII, 264 p.
Keywords: As Europe moves toward 1992 and full economic unity, and as Eastern Europe tries to find its way in the new economic order, the United States hesitates. Will the new European economic order be good for the U.S. or not? Such a question is exacerbated by world-wide changes in the technological order, most evident in Japan's new techno-economic power. As might be expected, philosophers have been slow to come to grips with such issues, and lack of interest is compounded by different philosophical styles in different parts of the world. What this volume addresses is more a matter of conflicting styles than a substantive confrontation with the real-world issues. But there is some attempt to be concrete. The symposium on Ivan Illich - with contributions from philosophers and social critics at the Penns- vania State University, where Illich has taught for several years - may suggest the old cliche of Old World vs. New World. Illich's fulminations against technology are often dismissed by Americans as old-world-style prophecy, while Illich seems largely unknown in his native Europe. But Albert Borgmann, born in Germany though now settled in the U.S., shows that this old dichotomy is difficult to maintain in our technological world. Borgmann's focus is on urgent technological problems that have become almost painfully evident in both Europe and America.